Community Enforcement with Endogenous Records - Pei, Harry (Review of Economic Studies, 2026)
I study repeated games with anonymous random matching where players can add or remove signals from their records. The ability to manipulate records introduces monotonicity constraints on players’ continuation values, under which sufficiently long-lived players will almost never cooperate. When players’ expected lifespans are intermediate, their ability to sustain cooperation depends on (i) whether their actions are complements or substitutes and (ii) whether manipulation takes the form of adding or removing signals.